Nuclear reactor physics and engineering - Lee, John C., 1941- (John Wiley & Sons, 2020)
"The book has been developed to introduce undergraduate and graduate students in nuclear engineering, as well as practicing engineers, to basic concepts of nuclear reactor physics and applications of the concepts to the analysis, design, control, and operation of nuclear reactors. The basic concepts are discussed and the associated mathematical formulations presented with the understanding that the reader has solid background in differential equations and linear algebra. A focus has been placed on the use of neutron diffusion theory, with a minimum use of the neutron transport equation, for the development of techniques for lattice physics and global reactor system studies. When the neutron transport equation is used, effort is made to stay with onedimensional forms of the Boltzmann equation and Legendre polynomials, without invoking the fullblown threedimensional Boltzmann equation and spherical harmonics. Recent developments in numerical algorithms, including the Krylov subspace method, for efficient solution of large matrix equations have been discussed as part of the numerical solution algorithms for the neutron diffusion equation"--